2020
DOI: 10.1021/acsami.0c16127
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Missing Linker Defects on the Thermal Conductivity of Metal–Organic Framework HKUST-1

Abstract: Although metal–organic frameworks (MOFs) are promising materials for gas storage and separation applications, the heat released during the exothermic adsorption process can potentially negatively impact their practical utility. Thermal transport in MOFs has not been widely studied, and among the relatively few reports on the topic, MOFs have either been assumed to be defect free or the presence of defects was not discussed. However, defects naturally exist in MOFs and can also be introduced intentionally. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…Therefore, in recent years, several studies have been performed to advance our understanding of heat transport in MOFs. They revealed that MOFs often display an unusually small negative or even positive temperature dependence of the thermal conductivity [20,21,[30][31][32] and they showed that defects such as missing linkers severely impede heat transport even at low concentrations [33]. Conversely, the interpenetration of frameworks results in materials whose thermal conductivities are essentially the sums of those of the sub-systems [34].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in recent years, several studies have been performed to advance our understanding of heat transport in MOFs. They revealed that MOFs often display an unusually small negative or even positive temperature dependence of the thermal conductivity [20,21,[30][31][32] and they showed that defects such as missing linkers severely impede heat transport even at low concentrations [33]. Conversely, the interpenetration of frameworks results in materials whose thermal conductivities are essentially the sums of those of the sub-systems [34].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this consideration, the organic ligands were selectively removed through a post-synthesis treatment (PST) of 2 by controlling the acid treatment time to obtain the missing-linker compound, denoted as 2-PST-V (V = 20, 40, 60, 120). [38][39][40][41][42] To illustrate the chemical composition and valences of the acid-treated samples, X-ray photoelectron spectroscopy (XPS) measurement was carried out (Figure S8). As shown in Figure 4a, the XPS spectra prove that two different N species belong to the CÀ N ( � 398.5 eV) and CoÀ N ( � 399.1 eV) groups are presented.…”
Section: Methodsmentioning
confidence: 99%
“…The low thermal conductivity observed in the present DUTs is close to the value (0.138 -0.174 Wm −1 K −1 ) of their ZIF counterparts, 27,28 but is much smaller than the value of some other SPCs such as MOF-5 (0.31 Wm −1 K −1 ), 24,25 and HKUST-1 (1.65 Wm −1 K −1 ). 33,34 Moreover, it is found that the thermal conductivity of DUT crystals generally decreases with increasing ligand length. For example, when the ligand length increases from one unit of phenylene in DUT-48 to four units of phenylene in DUT-151, the thermal conductivity is found to decline from 0.180 Wm −1 K −1 to 0.071 Wm −1 K −1 .…”
Section: Volumetric Heat Capacity and Vibrational Analysismentioning
confidence: 99%
“…However, compared with the gas adsorption property, the study of thermal transport in SPCs is still in its very early stage. To data, only the thermal conductivity of some conventional SPCs such as MOF-5, 23-26 ZIF-8, [27][28][29][30][31][32] and HKUST-1 21, 33,34 has been investigated in detail by experimental or computational approaches, while the thermal transport properties of the aforementioned DUT series still remain unknown. In addition, the existing studies mainly focus on the influence of gas and water adsorption, 29,34 framework architecture, 24,28,[35][36][37][38] defects, 33 and physical environment including pressure 18 and temperature 20 on the thermal conductivity of SPCs, little attention has been paid to the evolution of the thermal transport properties of SPCs during their dynamic process, i.e., the phase transition.…”
Section: Introductionmentioning
confidence: 99%